Restructuring vegetables into edible folding paper to improve nutrient intake - Sihombing, Monang; Putri, Femyta Anindya (Department of Agricultural Products Technology, Mulawarman University, 2026)
Vegetable consumption in Indonesia is low, particularly among preschool-aged children, who often do not meet daily intake recommendations. Sensory factors, such as taste, texture, and appearance, strongly influence children’s acceptance of vegetables. Previous studies have shown that modifying vegetables and using play-based learning can improve children’s interest. This study aimed to develop an edible folding paper made from vegetables, serving as both a nutritious food product and an interactive learning tool. Spinach, purple cabbage, and pumpkin were chosen for their good acceptance, nutrient content, and color appeal. The product was analyzed for macronutrients (proximate analysis) and micronutrients, including vitamin C, antioxidant activity, and iron (Fe) content. The results showed adequate levels of energy, protein, fat, and carbohydrates. Micronutrient analysis indicated 3.31 mg of iron, 53 mg of vitamin C, and 56.21% antioxidant inhibition per 100 g of product. Texture evaluation using origami-style folding confirmed good flexibility and tear resistance, supporting its function as an edible paper. Overall, the product retained substantial nutrients and could be folded into origami shapes without losing its structural integrity. This innovation has the potential to increase vegetable intake in children and improve dietary quality during early childhood.